Delegation of Authority within Medical Procedures from Doctors to Nurses Based on Health Law (Case Study Number 1167/Pid.B/2010/PN.Sda) - Adilla Meytiara Intan; Wahyu Andrianto; Rizky Muthiarani (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: This paper discusses the delegation of authority in medical actions, which are preventive, diagnostic, therapeutic and rehabilitative actions for patients delegated by doctors or dentists to nurses. This paper aims to identify and describe the arrangements regarding the procedures and requirements for the delegation of authority in medical treatment. In addition, it is also intended to identify the types of legal liability for medical actions that have been delegated. The method used in this study is qualitative with a statutory approach. The discussion is carried out through an analysis of decision number 1167/Pid.B/2010/PN.Sda to identify the responsibility of medical personnel and nursing staff if there is negligence or malpractice against the delegation of authority from medical personnel. Based on the results of the study, it was found that the delegation of authority in medical actions must be comprehensively regulated in the legislation, including in the event of an emergency.Keywords: delegation of authority, medical action, doctors, nurses, health law. Abstrak: Tulisan ini membahas mengenai pelimpahan kewenangan dalam tindakan medis, yakni merupakan tindakan berupa preventif, diagnostik, terapeutik dan rehabilitatif terhadap pasien yang dilimpahkan oleh dokter atau dokter gigi kepada perawat. Tulisan ini bertujuan untuk mengidentifikasi dan mendeskripsikan pengaturan mengenai tata cara dan persyaratan pelimpahan kewenangan dalam tindakan medis. Selain itu juga ditujukan untuk mengidentifikasi jenis-jenis pertanggungjawaban hukum terhadap tindakan medis yang telah dilimpahkan kewenangannya. Metode yang digunakan dalam penelitian ini kualitatif dengan pendekatan peraturan perundang-undangan. Pembahasan dilakukan melalui analisis putusan nomor 1167/Pid.B/2010/PN.Sda untuk mengidentifikasi pertanggungjawaban tenaga medis dan tenaga keperawatan apabila terdapat kelalaian atau malpraktik terhadap pelimpahan kewenangan dari tenaga medis. Berdasarkan hasil penelitian ditemukan bahwa pelimpahan kewenangan dalam tindakan medis harus diatur secara komprehensif di dalam peraturan perundang-undangan, termasuk jika terjadi kondisi emergency.Kata Kunci: pelimpahan kewenangan, tindakan medis, dokter, perawat, hukum kesehatan.